1992
DOI: 10.1073/pnas.89.6.2213
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom distribution of gp120 N-linked glycosylation sites important for infectivity of human immunodeficiency virus type 1.

Abstract: More than 20 consensus N-linked glycosylation sites occur in the gpl20 coding sequence of most isolates of human immunodeficiency virus type 1. Based on the N-linked glycosylation pattern of a well-characterized recombinant gpl20, it is likely that N-linked sugars are present at most, if not all, of the consensus glycosylation sites of the heavily glycosylated gpl20. In this study, we evaluated the relative importance of each of the 24 N-linked glycosylation sites of gpl20 in the molecular clone HXB2 to viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 26 publications
(23 reference statements)
2
81
2
Order By: Relevance
“…In fact, when tested in U87-CD4 ϩ CXCR4 ϩ and TZM-bl cell lines, the infectivity levels of pseudovirions bearing the mutated envelopes (⌬G1, ⌬G2, ⌬G3, and ⌬G123) were enhanced, ranging from 134 to 216% as compared with those of the WT virus. These data are consistent with previous findings from other laboratories (56,57); however, whether these mutant viruses also showed comparable or slightly enhanced infectivity in primary target cells such as PBMCs remains to be determined. Hence, the minor changes in CD4 binding capacity of these mutants do not appear to seriously alter the envelope functions and virus infectivity.…”
Section: Gp120 Proteins Lacking Single or Triple N-glycans Bind To CDsupporting
confidence: 83%
“…In fact, when tested in U87-CD4 ϩ CXCR4 ϩ and TZM-bl cell lines, the infectivity levels of pseudovirions bearing the mutated envelopes (⌬G1, ⌬G2, ⌬G3, and ⌬G123) were enhanced, ranging from 134 to 216% as compared with those of the WT virus. These data are consistent with previous findings from other laboratories (56,57); however, whether these mutant viruses also showed comparable or slightly enhanced infectivity in primary target cells such as PBMCs remains to be determined. Hence, the minor changes in CD4 binding capacity of these mutants do not appear to seriously alter the envelope functions and virus infectivity.…”
Section: Gp120 Proteins Lacking Single or Triple N-glycans Bind To CDsupporting
confidence: 83%
“…Moreover, Fung et al (1992) have found that a broadly neutralizing MAb, reacting with a conformational epitope in the V2 region, is dependent on gpl20-associated N-linked glycans for epitope binding. Carbohydrate-induced modulation of antibody binding, as described above, has been suggested to be a viral strategy for escaping immune responses against conserved regions (Bolmstedt et al, 1991 ;Lee et al, 1992). Benjouad et al (1992) have found that hyperimmune sera raised against desialylated gpl60 show increased reactivity to a synthetic peptide representing a region of gpl20 situated close to the class I epitopes defined in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Briefly, CEM cells (4.5 ϫ 10 5 cells per ml) were suspended in fresh culture medium and infected with HIV-1 at 100 CCID 50 (cell culture injective dose-50) per ml of cell suspension. Then 100 l of the infected cell suspension were transferred to microplate wells, mixed with 100 l of the appropriate dilutions of the test compounds, and further incubated at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Strains-HIV-1(III B )-infected CEM cell cultures were exposed to UDA at ϳ5 g/ml (ϳ 0.6 M), which is an ϳ2-4-fold higher concentration than its EC 50 (Fig. 1).…”
Section: Selection and Genotypic Characterization Of Uda-resistant Himentioning
confidence: 99%